Analisis Pengaruh Overconfidence dan Risk Tolerance terhadap Pengambilan Keputusan Investasi di Pasar Modal - M. Arief Setia Budi (Universitas Negeri Padang, 2025)
The study investigates the role of overconfidence and risk tolerance to decision making of investment. The location of the study is on the Faculty of Economics at the University of Muhammadiyah in Aceh Province. This study is in the form of an explanatory study with a quantitative model through filling out a questionnaire. The population in the study were all student investors and studying for undergraduate education from 6th semester to 8th semester from 2020-2023 class. This study collected 220 data for analysis from a total of 560 investors. Partial testing through t-test and simultaneous testing with f-test will be carried out in this research. The analysis in this research used the SPSS version 27th model with multiple linear regression. This study proves that overconfidence partially influences investment decision making. Risk tolerance has also been proven that overconfidence partially influences investment decision-making. Simultaneously, overconfidence and risk tolerance influences on investment decision making.